2020
DOI: 10.18203/2349-3933.ijam20202127
|View full text |Cite
|
Sign up to set email alerts
|

Oral anticoagulation therapy: current challenges in Indian scenario

Abstract: Over the past decade, the burden of thromboembolic diseases has increased in India; however, there is a huge gap between the diagnosis and treatment of these ailments. This is further complicated by the presence of various options for anticoagulation therapy and the absence of a clinical consensus on the use of these anticoagulants. To address this issue and establish consensus statements on the use of anticoagulation therapy in Indian settings, an expert consensus was developed in alignment with the latest av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…POCs devices facilitates more frequent testing of anticoagulation levels which in turn improves time in Therapeutic Range (TTR) and reduces bleeding and thrombotic complications in patients on oral anticoagulation therapy [12]. Though there are various PT/INR monitoring devices are available, cost of consumables hinders their use in the developing countries like India [7].…”
Section: Rmes000711 9(3)2021mentioning
confidence: 99%
See 2 more Smart Citations
“…POCs devices facilitates more frequent testing of anticoagulation levels which in turn improves time in Therapeutic Range (TTR) and reduces bleeding and thrombotic complications in patients on oral anticoagulation therapy [12]. Though there are various PT/INR monitoring devices are available, cost of consumables hinders their use in the developing countries like India [7].…”
Section: Rmes000711 9(3)2021mentioning
confidence: 99%
“…It was also observed that values obtained in the devices were on the higher side compare to the POC device used. Not many studies have been conducted on the POC devices in the Indian population [7]. Studies have reported variation in the INR values of POC devices compared to laboratory tests specifically in the high range of INR above 3.5 [15][16][17].…”
Section: Comparative Analysismentioning
confidence: 99%
See 1 more Smart Citation